Gender Differences in the Appetite Response to a Satiating Diet - Alexandra Bédard; Anne-Marie Hudon; Vicky Drapeau; Louise Corneau; Sylvie Dodin; Simone Lemieux (Journal of Obesity)
We examined gender differences in appetite sensations when exposed to Mediterranean diet (MedDiet) meals and determined whether there are gender differences in the change in the satiating properties of the MedDiet over time. Thirty-eight men and 32 premenopausal women consumed a 4-week isoenergetic MedDiet under controlled conditions. Visual analogue scales were used to measure perceived appetite sensations before and immediately after each meal consumed over the course of one day (Wednesday) of the first and the fourth week of intervention. Women reported greater decreases for desire to eat, hunger, and appetite score than men in response to the consumption of the MedDiet meals (gender-by-meal interactions, resp., P=0.04, P=0.048, and P=0.03). Fullness and prospective food consumption responses did not significantly differ between men and women. Between the first and the fourth week of intervention, premeal prospective food consumption increased with time in men (P=0.0007) but not in women (P=0.84; P for gender-by-time interaction = 0.04). These results indicate gender differences in appetite sensations when exposed to the MedDiet. These results may be useful in order to have a better understanding of gender issues for body weight management.